2022
DOI: 10.1108/mrr-03-2021-0194
|View full text |Cite
|
Sign up to set email alerts
|

Total quality management practices and corporate sustainable development in manufacturing companies: the mediating role of green innovation

Abstract: Purpose Manufacturing firms face increasing pressure to be more “greener” or environmentally friendly. Drawing upon the sustainable development (SD) theory and resource-based view, this study aims to examine the role of total quality management (TQM) and its effect on corporate SD (CSD). Also, this study focused on the mediating role of green innovation (GI). Design/methodology/approach This study used data from a time-lagged design with two waves that strengthened the hypothesized framework and used structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 96 publications
(143 reference statements)
0
20
0
Order By: Relevance
“…We employed the structural equation model (SEM) technique to analyse the conceptual model, which has been extensively used in previous studies ( Mehmood et al, 2019 ; Shang et al, 2021 ; Albloushi et al, 2022 ). The suggested model has a good fit, according to the fit indices (χ 2 / df = 877.475/158 = 1.694, CFI = 0.968, TLI = 0.965, and RMSEA = 0.042).…”
Section: Resultsmentioning
confidence: 99%
“…We employed the structural equation model (SEM) technique to analyse the conceptual model, which has been extensively used in previous studies ( Mehmood et al, 2019 ; Shang et al, 2021 ; Albloushi et al, 2022 ). The suggested model has a good fit, according to the fit indices (χ 2 / df = 877.475/158 = 1.694, CFI = 0.968, TLI = 0.965, and RMSEA = 0.042).…”
Section: Resultsmentioning
confidence: 99%
“…SMEs may specifically encounter barriers in acquiring and managing knowledge, such as a lack of formal knowledge management procedures, specialised human resources and clear knowledge-oriented leadership (Nunes et al , 2006; Donate and de Pablo, 2015; Albloushi et al , 2022). SMEs can overcome these barriers by exploiting knowledge acquisition mechanisms, such as inbound open innovation, to innovate their business model in turbulent times (Hock-Doepgen et al , 2021).…”
Section: Business Model Innovation and Open Innovationmentioning
confidence: 99%
“…It may be noted herein that although there have been studies relating quality management to sustainable development, only a few focused on the relationship between TQM and corporate sustainability (CS). For example, Albloushi et al. (2022) found that green innovation mediates the relation between TQM and corporate sustainability.…”
Section: Introductionmentioning
confidence: 99%